1994
DOI: 10.1007/bf00374853
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of two MDCK-cell subtypes as a model system to study principal cell and intercalated cell properties

Abstract: Madin-Darby canine kidney (MDCK) cells originate from the renal collecting duct and consist of different cell subtypes. We cloned two MDCK cell subtypes denominated as C7 and C11 with different morphology and different function. The two clones maintained their functional differences after cloning. C7 monolayers exhibit a high transepithelial resistance (Rte = 5648 +/- 206 omega.cm2, n = 20) and secrete K+ (delta K+ = 1.31 +/- 0.08 mmol/l, n = 10) into the apical medium. C11 monolayers display a low Rte (330 +/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
181
1
2

Year Published

1995
1995
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(191 citation statements)
references
References 30 publications
7
181
1
2
Order By: Relevance
“…Clones were expanded and screened for GFP fluorescence by confocal fluorescence microscopy. Similar experimental results were found in MDCK C7 cells (generous gift of Dr. Hans Oberleithner) (27) stably transfected with GFP-CFTR. Following establishment of cell lines, G418 was reduced to 150 g/ml and was removed 3-4 days prior to experimentation.…”
Section: Transfectionsupporting
confidence: 80%
“…Clones were expanded and screened for GFP fluorescence by confocal fluorescence microscopy. Similar experimental results were found in MDCK C7 cells (generous gift of Dr. Hans Oberleithner) (27) stably transfected with GFP-CFTR. Following establishment of cell lines, G418 was reduced to 150 g/ml and was removed 3-4 days prior to experimentation.…”
Section: Transfectionsupporting
confidence: 80%
“…Mouse B16F10 melanoma cells and ret transgenic melanoma cells 52,53 were cultured in DMEM or RPMI 1640 medium supplemented with 10% fetal calf serum (FCS) and 1% L-glutamine. The high-resistance C7 subclone of Madin-Darby canine kidney cells (MDCK-C7) 54 were cultured in supplemented MEM medium (PAA, Pasching, Austria).…”
Section: Cell Culturementioning
confidence: 99%
“…The present paper investigated the role of Cl -ions in H + ion transport across plasma membranes of a clone of cultivated MDCK cells, C11 cells, that were obtained by Gekle et al (11) and characterized as a model for renal-collecting duct intercalated cells. Experiments from our laboratory have shown that these cells possess Na + /H + exchangers, H + -ATPase and H + -K + -ATPase in their membranes, the latter transporters being demonstrated during experiments in 0 Na + solutions (12).…”
Section: Discussionmentioning
confidence: 99%
“…A subtype (clone) of MDCK cells denominated C11 (MDCK-C11), obtained from Dr. H. Oberleithner (Department of Physiology, University of Münster, Germany), was used (11). These cells were used from passage 74 to passage 82.…”
Section: Cell Culturementioning
confidence: 99%